The velocity and energy profiles of elite cross-country skiers executing downhill turns with different radii - Sandbakk, O.; Sandbakk, S. B.; Supej, M.; Holmberg, H. C. (International Journal of Sports Physiology and Performance, 2014)
This study examined the influence of turn radius on velocity and energy profiles when skidding and step turning during more and less effective downhill turns while cross-country skiing. Thirteen elite female cross-country skiers performed single turns with a 9- or 12-m radius using the skidding technique and a 12- or 15-m radius with step turning. Mechanical parameters were monitored using a real-time kinematic Global Navigation Satellite System and video analysis. Step turning was more effective during all phases of a turn, leading to higher velocities than skidding (P < .05). With both techniques, a greater radius was associated with higher velocity (P < .05), but the quality of turning, as assessed on the basis of energy characteristics, was the same. More effective skidding turns involved more pronounced deceleration early in the turn and maintenance of higher velocity thereafter, while more effective step turning involved lower energy dissipation during the latter half of the turn. In conclusion, the single-turn analysis employed here reveals differences in the various techniques chosen by elite cross-country skiers when executing downhill turns of varying radii and can be used to assess the quality of such turns.